2020
DOI: 10.3892/etm.2020.9277
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cells induce M2 polarization of macrophages through the upregulation of interleukin‑4

Abstract: Macrophages are divided into two types: M1-and M2-type macrophages. Both types of macrophages serve important roles during the process of inflammation. M1-type macrophages release various pro-inflammatory cytokines, such as IL-1, IFN-γ and other inflammatory mediators, such as nitric oxide, glutamate and reactive oxygen species to generate inflammation. In contrast, M2-type macrophages counteract the pro-inflammatory M1 conditions and promote tissue repair by secreting anti-inflammatory cytokines, such as IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Although many mysteries remain, the modulation of the inflammatory and immune microenvironment by NSCs may be a promising target for SCI repair. An in vitro co-culture study revealed that NSCs can induce macrophage polarization to M2 type, dependent on interleukin (IL)-4 ( Ji et al, 2020 ). Compared with pro-inflammatory M1 macrophages, M2 macrophages are considered anti-inflammatory and reparative ( Varga et al, 2016 ).…”
Section: Therapeutic Potential Of Nscs In Scimentioning
confidence: 99%
“…Although many mysteries remain, the modulation of the inflammatory and immune microenvironment by NSCs may be a promising target for SCI repair. An in vitro co-culture study revealed that NSCs can induce macrophage polarization to M2 type, dependent on interleukin (IL)-4 ( Ji et al, 2020 ). Compared with pro-inflammatory M1 macrophages, M2 macrophages are considered anti-inflammatory and reparative ( Varga et al, 2016 ).…”
Section: Therapeutic Potential Of Nscs In Scimentioning
confidence: 99%